Detecting local clusters of childhood malnutrition in the province of Marinduque using spatial scan statistics - Leyso, Novee Lor (Manila College of Public Health,University of the Philippines Manila, 2018)
Under-five malnutrition continues to persist in the Philippines, particularly in the province of Marinduque, with prevalence of some forms of malnutrition even worsening in recent years. Local spatial cluster detection using spatially-referenced data provides a spatial perspective in understanding childhood malnutrition as key in analyzing patterns of geographic variation, identification of factors associated to place or local characteristics, and for focused targeting of interventions. This study aimed to determine and evaluate spatial clusters of under-five malnutrition and its forms, across the province and within each municipality at the individual level using household location. Data from a province-wide household-based census conducted in 2014-2016 were utilized. Malnutrition was defined as weight-for-age z-score that fall outside the +-2 standard deviations from the median of the WHO reference population, and was classified into overweight, moderately and severely underweight. The Kulldorff?s elliptical spatial scan statistics using the binomial and multinomial models were used to locate clusters with high-risk of malnutrition, and clusters with high or low risk of different forms of malnutrition, respectively, while controlling for age and membership to 4Ps. Significant cluster of under-five malnutrition was found southwest of the province covering the municipalities of Boac, Buenavista, Gasan, and Torrijos. With the exception of Mogpog, at least one significant cluster of malnutrition was also identified within each municipality?mostly locate in coastal areas?suggesting apparent geographical variations across and within municipalities in the province. Three significant clusters across municipalities of Boac, Buenavista, and Gasan were found to have high-risk of over and undernutrition simultaneously, indicating existence of double burden of malnutrition within these communities. Therefore, specific programs and interventions should be focused on the identified high-risk clusters to maximize resources. Further studies are also recommended to determine factors affecting variations in childhood malnutrition considering the evidence of spatial clustering found in the study.
Thesis (Master of Science in Public Health (Biostatistics)--University of the Philippines Manila, December 2018.
Keywords: Malnutrition in children; Malnutrition